The Influence Of Transformational Leadership On Innovative Work Behavior Through Psychological Capital And Job Involvement As Intervening Variables - Rina Anindita; Desviana Ayu Lestari (Eduvest - Journal of Universal Studies, 2024)
This study explores the impact of transformational leadership on innovative work behavior at Jakarta Woman and Child Hospital, involving both medical and non-medical staff. With 281 respondents, the research uses purposive sampling for individuals with over a year of experience working directly or indirectly with patients. Utilizing Structural Equation Modeling-Partial Least Squares (SEM-PLS), the analysis reveals a positive influence of transformational leadership on innovative work behavior and job involvement. However, no significant relationships are found between transformational leadership and psychological capital, and between job involvement and innovative work behavior. Additionally, psychological capital does not act as a mediator in the relationship between transformational leadership and innovative work behavior. Managerially, enhancing transformational leadership is vital for fostering innovation and job involvement in hospitals, recommending strategies to improve psychological capital through positive work environments and training programs. Despite valuable insights, the study's limitations warrant further research for a broader understanding and identification of influencing factors within the healthcare industry.